Monopsony makes firms not only small but also unproductive: Why East Germany has not converged - Ruediger Bachmann; Christian Bayer; Heiko Stüber; Felix Wellschmied (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
When employers face a trade-off between being large and paying low wages - and in this sense have monopsony power - some productive employers decide to acquire few customers, forgo sales, and remain small. These decisions have adverse consequences for aggregate labor productivity. Using high-quality administrative data from Germany, we document that East German plants (compared to West German ones) face steeper size-wage curves, invest less into marketing, remain smaller, and are less productive. A model with labor market monopsony, product market power, and customer acquisition matching these features of the data predicts ten percent lower aggregate labor productivity in East Germany
Keywords: E20; E23; E24; J20; J42; J50; 330; aggregate productivity; plant heterogeneity; collective bargaining; monopsony power; size-wage curve; customer capital; size distortions